A broadly applicable high-throughput screening strategy identifies new regulators of Dlg4 (Psd-95) alternative splicing - Zheng, Sika; Damoiseaux, Robert; Chen, Liang; Black, Douglas L.

(untitled) (Genome Research, 2013)
Most mammalian genes produce multiple mRNA isoforms derived from alternative pre-mRNA splicing, with each alternative exon controlled by a complex network of regulatory factors. The identification of these regulators can be laborious and is usually carried out one factor at a time. We have developed a broadly applicable high-throughput screening method that simultaneously identifies multiple positive and negative regulators of a particular exon. Two minigene reporters were constructed: One produces green fluorescent protein (GFP) from the mRNA including an exon, and red fluorescent protein (RFP) from the mRNA lacking the exon; the other switches these fluorescent products of exon inclusion and exclusion. Combining results from these two reporters eliminates many false positives and greatly enriches for true splicing regulators. After extensive optimization of this method, we performed a gain-of-function screen of 15,779 cDNA clones and identified 40 genes affecting exon 18 of Discs large homolog 4 (Dlg4; also known as post-synaptic density protein 95 [Psd-95]). We confirmed that 28 of the 34 recoverable clones alter reporter splicing in RT-PCR assays. Remarkably, 18 of the identified genes encode splicing factors or RNA binding proteins, including PTBP1, a previously identified regulator of this exon. Loss-of-function experiments examining endogenous Dlg4 transcripts validated the effects of five of eight genes tested in independent cell lines, and two genes were further confirmed to regulate Dlg4 splicing in primary neurons. These results identify multiple new regulators of Dlg4 splicing, and validate an approach to isolating splicing regulators for almost any cassette exon from libraries of cDNAs, shRNAs, or small molecules.